Phytochemical Screening and Pharmacological Activities of Gentiana ornata from Lauribinayak, Rasuwa, Nepal - Maharjan, Sanam; Ranjitkar, Rajeshwor; Yadav, Parasmani; Bhandari, Devi Prasad (Journal of Plant Resources, 2024)
Gentiana ornata (Wall. ex G. Don) Griseb, also called decorated gentian or showy gentian, has been used as a decoction plant in temperate regions of Nepal. This work aims to evaluate the phytochemical properties, antioxidant values, and pharmacological properties of this plant collected from Lauribinayak, Gosainkunda Rural Municipality, Rasuwa, Nepal. The extract of whole plant was prepared by cold extraction process at 100% ethanol. Then, the qualitative preliminary phytochemical test of plant extract was performed to know its chemical constituents. The total phenolic content using Folin-Ciocalteu method, total flavonoid content using aluminium chloride colorimetric assay and antioxidant potential of the plant extract were also determined by using diphenylpicrylhydrazyl (DPPH) reagent. The pharmacological activities like oral acute toxicity test, antidiarrheal test and anti-ulcer test were also carried out in laboratory animals. The qualitative phytochemical screening showed the presence of flavonoids, steroids, glycosides, anthocyanin, alkaloids, terpenoids, and phenolic constituents. The total phenolic content, total flavonoid content and antioxidant assay value of this plant extract were 242.64±0.280 mg GAE/g, 39.23±0.005 mg QE/g and 42±0.072 µg/mL respectively. The extract showed no morbidity, mortality, toxicity signs, or symptoms in the oral acute toxicity test. Though it could not show considerable antidiarrheal effect by reducing gastrointestinal motility when compared to the standard drug, loperamide, it showed significant anti-ulcer effects by reducing gastric lesions when compared to the standard drug, sucralfate, which may be due to its mucosal protecting nature. Therefore, isolation and purification of phytochemicals responsible for the pharmacological activity of this plant have been recommended.